Effect of incorporation of heat-tolerant genes into Lohmann brown layers on egg production and quality under hot and humid environments - HAGAN, J K; ADOMAKO, K; OLYMPIO, S O (The Indian Journal of Animal Sciences, 2013)
A breed development strategy aimed at incorporating naked-neck and frizzle genes into Lohmann Brown layers to make them more productive even under warm and humid environment is underway at Akate Farms in Kumasi, Ghana. The present experiment was carried out to find out the effect of the genes on egg production in hot and humid environments. Three genetic groups comprising naked-neck, frizzle, their normally feathered sibs were obtained after 4 successive generations of crossing. In this present experiment, a total of 360, 16-week old pullets, 90 each of the 3 groups in addition to pure Lohmann Brown layer lines (used as the genetic control group) were selected randomly and assigned to a completely randomized design experiment with 3 replicates, with 30 birds in each replicate group and kept up to 72 weeks. The birds were kept in a partitioned open-sided deep-litter house constructed with sandcrete blocks with 30 pullets in each compartment. They were fed ad lib with layer diets containing 18% crude protein and 2800 Kcal ME/kg. Results obtained showed that the Lohmann brown layers (used as the control group) were significantly superior in terms of rate of lay, egg mass, egg weight and feed efficiency, but were however significantly inferior in egg quality as compared to their counterparts with the naked-neck and frizzle traits. Within the genetic groups with the heat-tolerant traits, the naked-neck layers out-performed their frizzle and normally feathered sibs in terms of the egg production parameters measured even though they all segregated from similar parents.